Українська письменницька публіцистика 1970 – 1980-х років - Павлюк, І. (Слово і Час, 2018)
Мета цієї статті – дослідження історично закономірних та ідеологічно деструктивних тенденцій
існування офіційної та опозиційної письменницької публіцистики в замкнутій тоталітарній
державі в контексті потенційного поглиблення в ній демократичних свобод. Методи дослідження:
феноменологічний (неупереджений опис), компаративний (порівняння публіцистичних текстів
досліджуваного періоду з текстами інших історичних періодів), психоаналітичний (зондування
архетипів), герменевтичний (проникнення в тексти), семіотичний (дешифровка знаків), ігровий
(розкриття механізмів розвитку феномену), деконструктивістський (пошук маргінальних значень
у текстах та сенсах свідомості). The purpose of this article is studying the historically determined and ideologically destructive
tendencies of the official and oppositional writers’ journalism. It existed in the isolated totalitarian state.
Although in the context of the potential growth of democratic freedoms there were attempts of finding
solutions for essential human problems. The methods of research are following: phenomenological
(unbiased description), comparative (comparison of journalistic texts of the period under study
with the texts of other historical periods), psychoanalytic (search for the archetypes), hermeneutic
(penetration into the meanings of the texts), semiotic (deciphering signs), game (revealing development
mechanisms of the phenomena), deconstructivist (search for marginal values in the texts and in the
meanings of consciousness). The Ukrainian literary journalism evolved in its contents and stylistics,
whether it existed abroad, or in the form of domestic publishing, or (the specific part of it) in a system
of total ideology, on the pages of the communist press. As concerns the totalitarian journalism, its first
distinctive feature is unification: all newspapers had to be similar (from the slogan “Proletarians of all
countries unite!”, the names of headings, type of layout to the style of presenting official or editorial
content). Therefore, for example, looking at any district newspaper, edited by the local committee of
the party, one might have an objective notion about hundreds of others. Цель этой статьи – исследование исторически
закономерных и идеологически деструктивных тенденций
существования официальной и оппозиционной
писательской публицистики в замкнутом тоталитарном
государстве в контексте потенциального углубления в
нем демократических свобод. Методы исследования:
феноменологический (беспристрастное описание),
компаративный (сравнение публицистических текстов
исследуемого периода с текстами других исторических
периодов), психоаналитический (зондирование
архетипов), герменевтический (проникновение в тексты),
семиотический (дешифровка знаков), игровой (раскрытие
механизмов развития феномена), деконструктивистский
(поиск маргинальных значений в текстах и смыслах
сознания).